Treatment with Antiangiogenic Drugs in Multiple Lines in Patients with Metastatic Colorectal Cancer: Meta-Analysis of Randomized Trials - R.-D. Hofheinz; U. Ronellenfitsch; S. Kubicka; A. Falcone; I. Burkholder; U. T. Hacker (Gastroenterology Research and Practice)
Background. In metastatic colorectal cancer (mCRC), continuing antiangiogenic drugs beyond progression might provide clinical benefit. We synthesized the available evidence in a meta-analysis. Patients and Methods. We conducted a meta-analysis of studies investigating the use of antiangiogenic drugs beyond progression. Eligible studies were randomized phase II/III trials. Primary endpoints were overall survival (OS) and progression-free survival (PFS). Secondary endpoints were the impact of continuing antiangiogenic drugs (i) in subgroups, (ii) in different types of compounds targeting the VEGF-axis (monoclonal antibodies versus tyrosine kinase inhibitors), and (iii) on remission rates and prevention of progression. Results. Eight studies (3,668 patients) were included. Continuing antiangiogenic treatment beyond progression significantly improved PFS (HR 0.64; 95%-CI, 0.55–0.75) and OS (HR 0.83; 95%-CI, 0.76–0.89). PFS was significantly improved in all subgroups with comparable HR. OS was improved in all subgroups stratified by age, gender, and ECOG status. The rate of patients achieving at least stable disease was improved with an OR of 2.25 (95%-CI, 1.41–3.58). Conclusions. This analysis shows a significant PFS and OS benefit as well as a benefit regarding disease stabilization when using antiangiogenic drugs beyond progression in mCRC. Future studies should focus on the optimal sequence of administering antiangiogenic drugs.